2011
DOI: 10.1007/s10488-011-0344-1
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Practices in a Time-Unlimited Intervention: The Perspectives of Practitioners in Assertive Community Treatment

Abstract: The Assertive Community Treatment (ACT) model for people with severe mental illness has typically been viewed as a time-unlimited intervention. Without a proscribed service duration, discharge from ACT largely depends on individual clients' situations and practitioners' discretion. We conducted semi-structured focus groups and interviews with practitioners to explore their discharge practices and considerations. Results highlight the heterogeneity of the clientele served in ACT, and therefore the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…They see discharge as a negative event for clients, a conclusion supported by recent data from Cuddeback et al (2013), and they work to obscure or disregard its finality. Chen and Herman (2012), in a qualitative study of clinicians in non-VA ACT programs, similarly found that clinicians had multiple concerns about discharge. Like the ACT clinicians in their study, these MHICM clinicians worry that other providers will not be sufficiently responsive to clients' needs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…They see discharge as a negative event for clients, a conclusion supported by recent data from Cuddeback et al (2013), and they work to obscure or disregard its finality. Chen and Herman (2012), in a qualitative study of clinicians in non-VA ACT programs, similarly found that clinicians had multiple concerns about discharge. Like the ACT clinicians in their study, these MHICM clinicians worry that other providers will not be sufficiently responsive to clients' needs.…”
Section: Discussionmentioning
confidence: 97%
“…Clinicians weigh their worries about current clients against the needs of the community of clients like them. Interestingly, the clinicians studied by Chen and Herman (2012) appear not to have commented on this responsibility to a community of clients. VA clinicians may have a more tangible sense than non-VA clinicians of the group of severely mentally ill veterans served by their own VA medical center.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because ACT program model standards emphasize “time-unlimited services” (Monroe-Devita, Teague, & Moser, 2011; Teague, Bond, & Drake, 1998), staff–client contact is continuously intensive, and the program is relatively inaccessible to new clients after the caseload has reached full capacity. For this reason, mental health agencies have questioned the premise of lifetime enrollment in ACT, and have begun planning for the gradual transfer of some ACT clients to less intensive support programs, to make space for new clients (Chen & Herman, 2012; Donahue et al, 2012; Rosenheck & Dennis, 2001; Salyers & Tsemberis, 2007). …”
mentioning
confidence: 99%